Targeted therapy for multiple gene mutations in multiple metastases of advanced gastric cancer: a case report - Zhang, Xin; Zhang, Xinran; Geng, Dandan; Zhao, Chenguang; Wang, Yingnan; Fan, Yao; Gao, Shasha; Wei, Jinmei; Zhang, Fengbin (Frontiers in Oncology, 2023)
In China, gastric cancer is the second most common cause of cancer-related death, after lung cancer. At present, the morbidity and mortality rates of gastric cancer are increasing, and targeted therapy for gastric cancer has become a research hotspot. Herein, we report a patient with multiple metastases from advanced gastric cancer. After identifying MET gene amplification, initial treatment induced regression of the tumor. However, in later stages, due to the overexpression or mutation of HER-2, KRAS, TP53, and other genes, the targeted drug therapy became ineffective, and the disease progressed rapidly, leading to the death of the patient.